Machine learning approaches for screening of materials in flexible electronic devices - Deng, Siyan (Nanyang Technological University, 2024)
In the rapidly evolving field of flexible electronics, the development of advanced materials is a cornerstone for innovation. Both active and substrate materials are key to the functionality and performance of flexible devices, which are becoming increasingly integral across various applications. The integration of machine learning into the field of flexible electronics represents a groundbreaking shift in materials science, allowing for accelerated discovery and optimization of materials. This thesis presents two pivotal projects that leverage machine learning to promote advancements in flexible electronics.